Mafalda : a social and political history of Latin America's global comic - Cosse, Isabella (Latin America in translation/en traducción/em tradução., 2019)
In Mafalda: A Social and Political History of Latin America's Global Comic Isabella Cosse examines the history, political commentary, and influence of the world-famous comic character Mafalda from her Argentine origins in 1964 to her global reach in the 1990s.